Clinical characteristics and risk factors for in‐hospital mortality of lung cancer patients with COVID‐19: A multicenter, retrospective, cohort study - Lei Nie; Kai Dai; Jiang Wu; Xia Zhou; Junjun Hu; Chao Zhang; Yan Zhan; Yu Song; Wen Fan; Zhimin Hu; Hongshan Yang; Qiong Yang; et al. (Thoracic Cancer)
Background Data on clinical, laboratory, and radiographic characteristics and risk factors for in‐hospital mortality of lung cancer patients with COVID‐19 are scarce. Here, we aimed to characterize the early clinical features of lung cancer patients with COVID‐19 and identify risk factors associated with in‐hospital mortality. Methods All consecutive lung cancer patients with laboratory‐confirmed COVID‐19 admitted to 12 hospitals in Hubei province, China, from 3 January to 6 May 2020 were included in the study. Patients without definite clinical outcomes during the period were excluded. Data on initial clinical, laboratory and radiographic findings were compared between survivors and nonsurvivors. Univariable and multivariable logistic regression analyses were used to explore the risk factors associated with in‐hospital mortality. Results Of the 45 lung cancer patients (median [interquartile range] age, 66 [58–74] years; 68.9% males) included, 34 (75.6%) discharged and 11 (24.4%) died. Fever (73.3%) and cough (53.3%) were the dominant initial symptoms, and respiratory symptoms were common. Lung cancer patients also presented atypical appearances of COVID‐19. In the multivariable analysis, prolonged prolongation prothrombin time (PT) (OR = 2.1, 95% CI: 1.00–4.41, P = 0.0497) and elevated high sensitivity cardiac troponin I (hs‐TNI) (OR = 7.65, 95% CI: 1.24–47.39, P = 0.0287) were associated with an increased risk of in‐hospital mortality. Conclusions Lung cancer patients with COVID‐19 have high in‐hospital mortality. Prolonged PT and elevated hs‐TNI are independent risk factors for in‐hospital mortality of lung cancer patients with COVID‐19. Key points Significant findings of the study Lung cancer patients with COVID‐19 have atypical early symptoms and imaging features. The prolonged prothrombin time and elevated high sensitivity cardiac troponin I are independent risk factors for in‐hospital mortality of lung cancer patients with COVID‐19. What this study adds This study characterizes the early clinical features of lung cancer patients with COVID‐19 in China, and identifies the risk factors associated with in‐hospital mortality of lung cancer patients with COVID‐19.